Association Between Achieved Low-Density Lipoprotein Cholesterol Levels and Long-Term Cardiovascular and Safety Outcomes: An Analysis of FOURIER-OLE. Issue 16 (13th February 2023) - Gaba, Prakriti; O'Donoghue, Michelle L.; Park, Jeong-Gun; Wiviott, Stephen D.; Atar, Dan; Kuder, Julia F.; Im, KyungAh; Murphy, Sabina A.; De Ferrari, Gaetano M.; Gaciong, Zbigniew A.; Toth, Kalman; Gouni-Berthold, Ioanna; et al.
Abstract : Background: Low-density lipoprotein cholesterol (LDL-C) is a well-established risk factor for atherosclerotic cardiovascular disease. However, the optimal achieved LDL-C level with regard to efficacy and safety in the long term remains unknown. Methods: In FOURIER (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk), 27 564 patients with stable atherosclerotic cardiovascular disease were randomized to evolocumab versus placebo, with a median follow-up of 2.2 years. In the open-label extension (FOURIER-OLE), 6635 of these patients were transitioned to open-label evolocumab regardless of initial treatment allocation in the parent trial and were followed for an additional median of 5 years. In this prespecified analysis, we examined the relationship between achieved LDL-C levels (an average of the first 2 LDL-C levels measured) in FOURIER-OLE (available in 6559 patients) and the incidence of subsequent cardiovascular and safety outcomes. We also performed sensitivity analyses evaluating cardiovascular and safety outcomes in the entire FOURIER and FOURIER-OLE patient population. Multivariable modeling was used to adjust for baseline factors associated with achieved LDL-C levels. Results: In FOURIER-OLE, 1604 (24%), 2627 (40%), 1031 (16%), 486 (7%), and 811 (12%) patients achieved LDL-C levels of <20, 20 to <40, 40 to <55, 55 to <70, and ≥70 mg/dL, respectively. There was a monotonic relationship between lower achieved LDL-C levels—down to very low levels <20 mg/dL—and a lower risk of the primary efficacy end point (composite of cardiovascular death, myocardial infarction, stroke, hospital admission for unstable angina or coronary revascularization) and the key secondary efficacy end point (composite of cardiovascular death, myocardial infarction, or stroke) that persisted after multivariable adjustment (adjusted P trend <0.0001 for each end points). No statistically significant associations existed in the primary analyses between lower achieved LDL-C levels and increased risk of the safety outcomes (serious adverse events, new or recurrent cancer, cataract-related adverse events, hemorrhagic stroke, new-onset diabetes, neurocognitive adverse events, muscle-related events, or noncardiovascular death). Similar findings were noted in the entire FOURIER and FOURIER-OLE cohort up to a maximum follow-up of 8.6 years. Conclusions: In patients with atherosclerotic cardiovascular disease, long-term achievement of lower LDL-C levels, down to <20 mg/dL (<0.5 mmol/L), was associated with a lower risk of cardiovascular outcomes with no significant safety concerns. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01764633.